Mesoporous titania: Effect of thermal treatment on the texture and acidic properties - Pizzio, Luis Rene (2005)
Mesoporous titania materials have been synthesized by using urea as low cost template via sol-gel reactions of titaniumisopropoxide, followed by removing the urea by extraction with water. They were characterized by FT-IR, XRD, DTA-TGA and BET. The SBET of the solids increases with the increase of the urea content and decreases with the increase of the calcination temperature. The XRD patterns of the samples exhibit only the characteristic peaks of the anatase phase. The crystallinity increased when the temperature went up. The acidic characteristics of the samples were evaluated by TPD and DRIFTS of adsorbed pyridine. The total amount of pyridine adsorbed decreases in parallel with the increase of the calcination temperature. The samples displayed two types of Lewis acid sites, with which pyridine interacts via coordination bonding. © 2004 Elsevier B.V. All rights reserved.